2022
DOI: 10.3390/ijms23073413
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Potential of Cerrado Plants on Different Organisms

Abstract: Cerrado has many compounds that have been used as biopesticides, herbicides, medicines, and others due to their highly toxic potential. Thus, this review aims to present information about the toxicity of Cerrado plants. For this purpose, a review was performed using PubMed, Science Direct, and Web Of Science databases. After applying exclusion criteria, 187 articles published in the last 20 years were selected and analyzed. Detailed information about the extract preparation, part of the plant used, dose/concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…Phytochemical analysis has revealed that B. pilosa leaf extracts contain a broad chemical constitution, suggesting that the cytotoxicity activity could be related to secondary metabolites such as terpenes, flavonoids, and alkaloids [ 97 ]. In previous studies, it was suggested that the strong in vitro activity at high concentrations is related to other mechanisms, such as interference with mitochondrial or lysosomal function [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical analysis has revealed that B. pilosa leaf extracts contain a broad chemical constitution, suggesting that the cytotoxicity activity could be related to secondary metabolites such as terpenes, flavonoids, and alkaloids [ 97 ]. In previous studies, it was suggested that the strong in vitro activity at high concentrations is related to other mechanisms, such as interference with mitochondrial or lysosomal function [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Sapindaceae) is an endemic species from Brazil popularly known as 'tingui' or 'timbó'. It is the only species of the Magonia genus and is widely distributed in the states of Goiás, Mato Grosso, Mato Grosso do Sul, and Minas Gerais [27] in the Brazilian savannah (the Cerrado) [28]. The fruits and seeds of the plant are used to prepare soap for the treatment of dermatitis, lice infestations, and as an insecticide and larvicide [29].…”
Section: Introductionmentioning
confidence: 99%